The Role of Art-Based TVET in Enhancing Career Readiness and Economic Growth in Ghana - Gbadegbe, Richard Selase; Amewu, Joseph; Krampa, Elikem; Vigbedor, Divine; Godomey, Bernard Sprehe (Journal of Technical Education and Training, 2026)
Although art-based Technical and Vocational Education and Training (TVET) possess substantial potential to drive economic transformation, its specific role in enhancing career readiness and stimulating economic growth in Ghana remains underexplored in empirical literature. Grounded in Human Capital Theory (HCT), this study examines the structural relationships between art-based TVET, career readiness, and economic growth. Using a purposive sampling technique, data were collected from 251 respondents through an online survey questionnaire. The study employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed model and assess the predictive relationships among the constructs. The findings reveal that career readiness significantly enhances employability and contributes to economic growth through real-world training, entrepreneurial education, and practical skills development. Although TVET specialization demonstrates a positive relationship with employability and economic outcomes, its effect is comparatively weaker than that of career readiness, indicating that not all specializations are equally aligned with labour market demands. The study’s primary contribution lies in extending Human Capital Theory to the context of art-based TVET in Ghana by empirically demonstrating that career readiness serves as a critical mediating mechanism linking creative vocational education to economic growth. By shifting the discourse from general TVET outcomes to the strategic role of career readiness within art-based programmes, the study provides novel evidence that informs curriculum reform, industry–education collaboration, and policy direction in Ghana and similar developing economies.